Growth, spectroscopic and laser properties of a new Yb0.05:Lu0.03Y0.92PO4 mixed orthophosphate crystal. (August 2022) - Lu, Jingyao; Zheng, Fei; Cao, Shuxuan; Che, Yang; Li, Jianhong; Sun, Shijia; Gao, Jia; Hu, Chen; Teng, Bing; Zhao, Jiaqi; Sun, Ruyi; Zhong, Degao
Highlights: A new mixed orthophosphate laser crystal of Yb0.05 :Lu0.03 Y0.92 PO4 was grown. The spectral parameters of Yb0.05 :Lu0.03 Y0.92 PO4 crystals were calculated in detail. A maximum CW laser output power of 0.81 W with slope efficiency of 46.4% was achieved. Abstract: A new mixed orthophosphate crystal of Yb0.05 :Lu0.03 Y0.92 PO4 was grown by high temperature solution method. The crystal structure, polarization absorption and emission spectra, and fluorescence lifetime were measured and investigated in detail. Continuous-wave (CW) laser action of the mixed crystal was achieved in a simple plane-parallel resonator under diode pumping, producing a maximum CW output power of 0.81 W with a pump power of 2.18 W, the slope and optical-to-optical efficiencies being respectively 46.4% and 39.6%. The wide emission spectrum of the mixed crystal also indicates that it may be of some potential applications in the generation of mode-locked femtosecond pulsed lasers.